Right atrial mass-not always a myxoma!! - Girish Manjunath; S.N. Nagendra Prakash; Shivaram Beladakere Krishnappa; Prakash Aroor Sarvotham Rao; Venu Gopal Anandaswamy (IHJ Cardiovascular Case Reports, 2019)
Teratomas are an extremely rare entity among cardiac neoplasms. Most of the cases reported so far in the literature are of extracardiac origin and in the paediatric population. We report a case of Intracardiac teratoma in an adult patient.